PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI BADAN KETAHANAN PANGAN DAN PELAKSANA PENYULUHAN KABUPATEN MAMUJU UTARA - Abdul Gafur (Katalogis, 2018)
In an organization, both formal and non-formal, the human role are very dominant as a driving force in the running of the organization to achieve the goals that have been set. Human resources holds a very important role where human resources is seen as a major driving factor in determining the success of an organization. This study used motivational variables consisting of the factors of motivator and hygiene as independent variables and the employee performance factor as dependent variable. The type of research used in this study was descriptive and quantitative. The research location is North Mamuju Board for Food Security and Counselors. The samples involved in this study were 75 people who were employees at various levels. The data used in this study consisted of primary and secondary data. Questionnaires was used as a medium to get data from the respondents. Data were analyzed using multiple linear regression method. The results of this study showed that motivation comprising the factors of motivator and hygiene simultaneously had positive and significant influence on employee performance. Partially, the motivator factor had positive and significant relationship to employee performance. Meanwhile, the hygiene factor partially did not had relationship to employee performance. The results of this study could be used as an input by North Mamuju Board for Food Security and Counselors in improving employee performance. The results also can strengthen motivation theories that had been studied in several research. Future studies should include other variables in order that generalization of this theory can be strengthened in relation to the performance aspect.